2013
DOI: 10.1364/oe.21.000927
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced distribution of a wave-packet in lattices with disorder and nonlinearity

Abstract: We show, numerically and experimentally, that the presence of weak disorder results in an enhanced energy distribution of an initially localized wave-packet, in one- and two-dimensional finite lattices. The addition of a focusing nonlinearity facilitates the spreading effect even further by increasing the wave-packet effective size. We find a clear transition between the regions of enhanced spreading (weak disorder) and localization (strong disorder).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
7
21
0
Order By: Relevance
“…For 2D systems, we do not expect to experimentally observe similar results. As a larger disorder is required to observe localization in 2D lattices [12], the whole picture will be scaled up and the different polarizations will essentially show the same. The transition to localization in ID is more abrupt and, therefore, the different polarizations really experience different dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 2D systems, we do not expect to experimentally observe similar results. As a larger disorder is required to observe localization in 2D lattices [12], the whole picture will be scaled up and the different polarizations will essentially show the same. The transition to localization in ID is more abrupt and, therefore, the different polarizations really experience different dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the first experim ental dem onstration o f A nderson localization w as perform ed using optical lattices [7,8]. D isordered lattices exhibit a w ealth o f transport phenom ena, such as disorder-induced edge states [9], disorder-enhanced transport [ 10,11 ], and the interplay betw een nonlinearity and disorder [12].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized on-site energy for the diagonal disorder can be introduced by a controlled variation of the width [16] or the refractive index [45,46] of each waveguide while keeping the tunneling rates between waveguides constant. Randomized tunneling strength can be introduced by a controlled variation of the separation between adjacent waveguides [2,19,47], while keeping the symmetry with respect to the diagonal axis. For this off-diagonal disorder, identical waveguides should be employed except in the diagonal axis where a difference between the refractive indices of the diagonal (n d ) and offdiagonal (n 0 ) waveguides effectively leads to the interaction U ∼ (n 0 − n d ).…”
Section: Figmentioning
confidence: 99%
“…In fact, Anderson himself first noticed the importance of interaction in localization phenomena [8] and launched a theoretical investigation in collaboration with Fleishman [9]. Recently, advances in technology have reinvigorated theoretical [10,11] and experimental [12][13][14][15][16][17][18][19] interest on this subject. For the special case of two interacting particles in a random one-dimensional (1D) potential, Shepelyansky has investigated the interplay of disorder and interaction and concluded that interaction modifies (weakens) localization [20].…”
mentioning
confidence: 99%
“…When nonlinearity is introduced, the problem becomes significantly more complicated: on the one hand, nonlinearity can lead to self-trapping and the formation of discrete breathers, thus enhancing localization [3]. On the other hand, nonlinearity can also destroy the phase coherence which is essential for Anderson localization, which can result in chaotic dynamics and enhanced spreading [4], [5], [6], [7]. There is still no complete picture of the different nonlinear dynamical regimes [8].…”
Section: Introductionmentioning
confidence: 99%